2012
DOI: 10.7589/0090-3558-48.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Short-Term Dehydration and Sublethal Acute Oral Dicrotophos Exposure Confounds the Diagnosis of Anticholinesterase Exposure in Common Quail (Coturnix Coturnix) Using Plasma Cholinesterase Activity

Abstract: ABSTRACT:Common Quail (Coturnix coturnix) were subjected to controlled and replicated experiments in the summer of 2008 to investigate the effects of short-term dehydration on cholinesterase activity in brain and plasma and the interaction between dehydration and exposure to the organophosphorus pesticide dicrotophos in these same tissues. Our objective was to determine if dehydration could confound the diagnosis of anticholinesterase exposure using inhibition of cholinesterase activity in quail tissues. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Heffernan et al (2012) reported that dehydration caused a significant increase in plasma ChE activity. In their study in quail (Coturnix coturnix), the combination of dehydration and the OP dicrotophos exposure produced plasma ChE activity that was not significantly different from reference and pre-exposure values, confounding the diagnosis of anticholinesterase exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heffernan et al (2012) reported that dehydration caused a significant increase in plasma ChE activity. In their study in quail (Coturnix coturnix), the combination of dehydration and the OP dicrotophos exposure produced plasma ChE activity that was not significantly different from reference and pre-exposure values, confounding the diagnosis of anticholinesterase exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A larger sample size would be required to explore and validate such findings further in relation to Carnaby's Black-Cockatoos. Clinicians responsible for diagnosis of anticholinesterase exposure in birds should be aware that dehydration may mask the effect of anticholinesterases on plasma ChE activity, that methods to adjust plasma ChE activities for the confounding effects of dehydration have been developed, and that these methods will facilitate the diagnosis of anticholinesterase exposure in dehydrated, exposed birds (Heffernan et al 2012).…”
Section: Discussionmentioning
confidence: 99%